Extreme proximal migration of dislocated lunate over carpal ligament – A case report - Jun-Mo Lee; Jong-Kil Kim; Kwang-Bok Lee (Acta Orthopaedica et Traumatologica Turcica, 2017)
Dislocation of the lunate and proximal pole of the scaphoid with displacement of the fragments proximal to the radiocarpal joint, characterized as a total dislocation, is very rare, with only six cases reported. Dislocated lunate are generally located around the radiocarpal joint or within carpal ligament. However, there have been no reports of dislocated lunate over the carpal ligament. We present a patient with volar dislocation of the lunate that featured extreme migration to approximately 6 cm proximal to flexor digitorum superficialis through the transcarpal ligament. Keywords: Lunate, Dislocation, Proximal migration